The Threats of Ukraine Financial Security: Identification and Systemization (Economics and region, 2019)
Place of monitoring and control of risks of financial stability of the state in the system of ensuring financial security of the state was substantiated. Methods of identifying threats to Ukraine's financial security through the current and strategic analysis of financial system development indicators were considered. Tendencies of economic development of Ukraine in the context of revealing sources of threats to financial stability of the state were analyzed. Dynamic analysis of the actual values of the financial security indicators of Ukraine as a whole and its separate components had been carried out. Threats to Ukraine's financial security were identified based on comparative and trend analysis. Reasons for the critical state of debt, banking and monetary security in the financial structure and the preconditions for the emergence of systemic threats had been investigated. Systematization of risks and threats to Ukraine's financial security by its components had been carried out. Influence of systemic threats in the financial sphere on the economic security of the state was generalized. International experience of monitoring financial stability of the state was analyzed. Additional risks to the national financial system are associated with the globalization and digitization of the state financial system that are not taken into account by valid methodological recommendations for calculating the level of economic security of Ukraine were highlighted.
Keywords: financial security; state economic security; risk; threat; threat indicator; financial system